The inertial loads of a telescopic boom of a truck crane - Volianiuk, V. О.; Gorbatyuk, Ie. V.; Mishchuk, D. О.; Волянюк, В. О.; Горбатюк, Є. В.; Міщук, Д. О. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The analysis of existing research and publications in which the main problem is highlighted, namely, that many factors are not taken into account when calculating the inertial loads of the car crane arrows. Accounting for these factors will allow you to more accurately determine the inertial loads of the boom of the car crane, to carry out strength-hunches of the elements of the boom and the selection of components of its drive mechanisms. Goal. The purpose of the work is to determine the inertial navan-loads acting on the load and arrow of the automobile-side crane during the unstable movement of its. Methodology. To calculate the inertial loads, the technique of determining the total inertial loads of the car crane boom during joint operations in accordance with the Safety Regulations has been developed. Total inertial loads were determined for the following cases: joint lifting (lowering) of cargo and arrows; lifting the load and turning the boom; lifting and turning the arrow. Results. The resulting dependencies for determining the inertial loads of the rotary boom of the car crane will allow more accurately taking into account multiple factors to calculate the values of these loads in order to conduct strong calculations of the boom, the selection of its components mechanisms. Originality. When calculating inertial loads, the weight and length of the boom are taken into account; weight and height of lifting of cargo; the radius of the arrow crane; rotation speed of the rotary part of the crane; speed of movement of cargo and arrows; start time and braking of cargo lifting mechanisms, change of departure and turn of the boom. The advantage of this technique is its originality. Practical value. The use of this technique allows more accurately taking into account multiple factors to determine the values of the inertial loads of the automobile crane during the unstable movement of the cargo lifting mechanisms, changes in the discharge of the boom and its rotation in order to conduct strong-standing calculations of the boom elements, the selection of its components.
Інерційні навантаження телескопічної стріли автомобільного крана
Keywords: crane; boom; load; moment; inertia; кран; стріла; вантаж; момент; інерція; 621.87; 10.30977/AT.2019-8342.2021.0.49.01